Torvströ till svenska mjölkkor - Andersson, Karin (SLU/Dept. of Animal Nutrition and Management (until 231231), 2007)
Peat litter is a soft material with high absorbency. About hundred years ago many farmers in Sweden used peat litter to their dairy cows. After the World War II the use of peat litter decreased and the farmers used more straw. Nowadays (year 2007), when it is harder to find straw and sawdust to buy, peat litter is advancing again. The purpose with this study is to investigate peat as a litter to dairy cows. The study consists of two parts, one station experiment and one interview with 20 farmers that had used or were using peat litter.